The Effect of Business Networks, Product Innovation, and Business Competition on the Development of Micro, Small and Medium Enterprises (MSMEs) In Boven Digoel District - Rita Anggraini; Abdul Rahman Kadir; Mursalim Nohong (Hasanuddin Journal of Business Strategy, 2020)
The purpose of this study is to determine and analyze the effect of business networks, product innovation and business competition on the development of MSMEs in Boven Digoel Regency either partially or simultaneously. This study will explain the causal relationship between variables through hypothesis testing. In this study, the analytical method used is path analysis (Path Analysis) using the SPSS program. The results of the study found that the variables of business networks, product innovation, and business competition partially have a significant effect on the development of small and medium enterprises in Boven Digoel Regency, which means that when the Business Network is improved it will have a significant effect on the development of Small and Medium Enterprises in Boven Digoel Regency. Furthermore, the variables of Business Network, Product Innovation, and Business Competition together (simultaneously) have a significant effect on the development of Small and Medium Enterprises in Boven Digoel district.